Adolescent-to-Parent Abuse : Current Understandings in Research, Policy and Practice - Holt, Amanda (Book collections on Project MUSE., 2013)
"While much has been written about the problematic behaviour of young people and their families, there has been silence on the problem of young people behaving abusively towards their parents, which may take the form of physical, economic and/or emotional abuse. This is the first academic book to focus on adolescent-to-parent abuse and brings together international research and practice literature and combines it with original research to identify and critique current understandings in research, policy and practice. It discusses what we know about parents' experiences of adolescent-to-parent abuse and critically examines how it has been explained from psychological, sociological and sociocultural perspectives. It also outlines how policymakers and practitioners can usefully respond to the problem. This unique book adopts a range of theoretical and practice perspectives. Written in an accessible style, it is an essential tool for academics, policymakers and professionals with an interest in domestic violence, child protection and youth offending."--Publisher's website.